2021
DOI: 10.3390/polym13172887
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Urea Nanocomposite for Improved Fertilizer Applications: The Effect on the Soil Enzymatic Activities and Microflora Dynamics in N Cycle of Potatoes (Solanum tuberosum L.)

Abstract: The impact of polymer-based slow-release urea formulations on soil microbial N dynamics in potatoes has been sparingly deciphered. The present study investigated the effect of a biodegradable nano-polymer urea formulation on soil enzymatic activities and microflora involved in the N cycling of potato (Solanum tuberosum L.). The nano-chitosan-urea composite (NCUC) treatment significantly increased the soil dehydrogenase activity, organic carbon content and available potassium compared to the conventional urea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 72 publications
0
11
1
Order By: Relevance
“…Some studies have reported that the soil microbial community can be significantly compromised upon exposure to nanomaterials [ 44 ]. However, these studies were conducted to understand the impact on soil microbial community of metal/metal oxide nanomaterials [ 45 ] and polymeric nanoparticles [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that the soil microbial community can be significantly compromised upon exposure to nanomaterials [ 44 ]. However, these studies were conducted to understand the impact on soil microbial community of metal/metal oxide nanomaterials [ 45 ] and polymeric nanoparticles [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morphological characteristics of nanocarriers may influence nutrient transport through the surface of the membranes, which is crucial in order to demonstrate the application and usefulness of nano-fertilizers, as shown in Table 1 . It was found that nCHT has a good effect on morphological and physiological features in both germinating seed and foliar treatment to boost the growth of seedlings, biomass, germination capacity, and seed vigor index in chickpea, maize, and tomato seedlings [ 28 , 79 , 80 ]. Plant physiology and performance was found to be improved by increasing the density of certain nanoparticle surfaces [ 3 ]; application of nano-Zn resulted in significant modifications in rice biomass, relative water content [ 81 ], sunflower biomass [ 82 ], wheat grain yield under stress [ 83 ], and maize yield under drought [ 84 ] by increasing NUE [ 85 ] through alteration in physiological characteristics [ 86 ], including cell division, cell wall extension, and aquaporin in tobacco [ 87 ], shown in Table 1 and Figure 1 , Figure 2 and Figure 3 .…”
Section: Nano-fertilizers Mitigate Abiotic Stressesmentioning
confidence: 99%
“…In addition to the environmental issues, the release of nutrients such N in soil has to be integrated within the plant growth needs [ 152 , 162 , 163 ]. In this context, different formulations of urea increase the soil microbial activity compared to the conventional one, such as polyolefin-coated controlled release (CR) urea for maize crops or encapsulated urea into chitosan polymer for potato growth, due to the N content increasing [ 164 ].…”
Section: Remediation Of Water/soil Systemsmentioning
confidence: 99%
“…In this context, different formulations of urea increase the soil microbial activity compared to the conventional one, such as polyolefin-coated controlled release (CR) urea for maize crops or encapsulated urea into chitosan polymer for potato growth, due to the N content increasing [ 164 ]. It was observed that the great amounts of nitrogen-cycling microbial communities for potato crops are affected by the proper controlled release of N nutrient using a chitosan polymer–urea encapsulated fertilizer [ 152 ].…”
Section: Remediation Of Water/soil Systemsmentioning
confidence: 99%